Five‐year review of absconding in three acute psychiatric inpatient wards in Australia. (1st December 2014) - Gerace, Adam; Oster, Candice; Mosel, Krista; O'Kane, Deb; Ash, David; Muir‐Cochrane, Eimear
Abstract Absconding, where patients under an involuntary mental health order leave hospital without permission, can result in patient harm and emotional and professional implications for nursing staff. However, Australian data to drive nursing interventions remain sparse. The purpose of this retrospective study was to investigate absconding in three acute care wards from January 2006 to June 2010, in order to determine absconding rates, compare patients who did and did not abscond, and to examine incidents. The absconding rate was 17.22 incidents per 100 involuntary admissions (12.09% of patients), with no significant change over time. Being male, young, diagnosed with a schizophrenia or substance‐use disorder, and having a longer hospital stay were predictive of absconding. Aboriginal and Torres Strait Islander patients had higher odds of absconding than Caucasian Australians. Over 25% of absconding patients did so multiple times. Patients absconded early in admission. More incidents occurred earlier in the year, during summer and autumn, and later in the week, and few incidents occurred early in the morning. Almost 60% of incidents lasted ≤24 hours. Formulation of prospective interventions considering population demographic factors and person‐specific concerns are required for evidence‐based nursing management of the risks of absconding and effective incident handling when they do occur.